Cognitive Status and Risk Factors for Cognitive Impairment in Dialysis Patients - A. Е. Khrulev; D. D. Tolbuzova; E. A. Plokhenko; P. A. Egorova; S. N. Sorokoumova; O. V. Suvorova; D. S. Yankevich (Общая реаниматология)
The number of dialysis patients is increasing every year and is estimated to be more than 2 million, with an annual increase of 6–12% in dialysis programs. There is a high correlation between cognitive impairment and mortality in dialysis patients, which suggests the relevance of screening cognitive functions in dialysis patients using diﬀerent neuropsychological scales.Aim of the study was to test the cognitive status and identify cognitive impairment in patients with terminal stage of chronic kidney disease treated using program hemodialysis, as well as to evaluate risk factors for cognitive impairment in this category of patients.Material and methods. 83 patients aged 28 to 78 years (mean age 56.7±13.7 years) were examined. The main group included 53 people who received program hemodialysis, of them 23 men and 30 women. The mean age of patients in this group was 58.3±13.3 years. The control group composed of 30 individuals without kidney diseases, including 13 men and 17 women. The mean age in the control group was 53.6±14.9 years. The MoCA and SLUMS scales were chosen for detecting cognitive impairment and assessment of neuropsychological status. We used mathematical methods of research data processing such as inductive statistics and correlation analysis.Results. Cognitive impairment was found to be signiﬁcantly more frequent in dialysis patients (75.5–81.1% of cases, P=0.05) compared to those without kidney pathology. The SLUMS scale was shown to be more sensitive than MoCA (P=0.05, CI 95.0%). The risk factors of cognitive impairment in dialysis patients included increased dialysis duration, age (rs=–0.298) and low estimated urea dialysis adequacy index (Kt/V less than 1.2).Conclusion. A high risk of cognitive impairment is common in dialysis patients. For its timely detection,  the screening neuropsychological test are recommended to be used by clinicians. Cognitive impairment, diagnosed by the tests, is an indication for a specialist consultation.